Income effects and the welfare consequences of tax in differentiated product oligopoly - Rachel Griffith; Lars Nesheim; Martin O'Connell (Quantitative Economics, 2018)
Random utility models are widely used to study consumer choice. The vast majority of applications assume utility is linear in consumption of the outside good, which imposes that total expenditure on the subset of goods of interest does not affect demand for inside goods and restricts demand curvature and pass-through. We show that relaxing these restrictions can be important, particularly if one is interested in the distributional effects of a policy change, even in a market for a small budget share product category. We consider the use of tax policy to lower fat consumption and show that a specific (per unit) tax results in larger reductions than an ad valorem tax, but at a greater cost to consumers.
Keywords: H20; L13; 330; Income effects; compensating variation; demand estimation; oligopoly; pass-through; fat tax